Supervisory Strategy of Inner Madrasah Aliyah Education Improving the Professionalism of Madrasah Heads - Arif Hidayatulloh; Akhyak Akhyak; Asrop Safi’i (Journal of Instructional and Development Researches, 2023)
Education is one of the efforts to improve human quality. One of the elements that make education more quality, is human resources, namely teachers, prinsiple of madrasah, educators and education staff, namely teachers, other educators, madrasah principle, and madrasah supervisors. To improve the professionalism of teachers and madrasah principals, supervisory guidance is needed as a coach. In carrying out their supervisory duties, madrasah supervisors need strategies that will be used in carrying out their supervisory duties.Data collection in this study used in-depth interviews, observation, and documentation techniques. Data analysis was carried out in two stages, namely single site data analysis and cross site data analysis. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The technique for checking the validity of the data is through credibility, transferability, dependability, and confirmability.The results of this study indicate that: 1) The planning strategy of madrasah supervisors consists of: (a) Forming a teamwork to formulate a supervisory program. (b) Planning the program according to the needs of the madrasa principal based on the previous year's evaluation and carried out collaboratively. (2) Implementation strategy of madrasah supervisors, namely: (a) Carrying out periodical coaching and mentoring at least 3 times a year, namely at the beginning of the year, in the middle and at the end of the year. (b) Carry out monitoring of 8 SNPs and supervision and to the head of the madrasa in accordance with the planning schedule, 3) The supervisor's evaluation strategy, namely: (a) Carrying out a coaching evaluation and analyzing the results after providing guidance to the head of the madrasa. (b) Evaluation and analysis of monitoring results is carried out by the development supervisor in collaboration with other supervisors. The formal finding of this research is the Periodic Collaborative Madrasah Supervisory Strategy.